Left to Tell: Discovering God Amidst the Rwandan Holocaust. California: Hay House, Inc., 2006, 215 pp (Hekima Review, 2008)
In this book, Immaculée Ilibagiza shares the power of faith in God through her moving experience of the Rwandan genocide. God saved her life for a reason: “He left me to tell my story to others and show as many people as possible the leading power of his Love and Forgiveness” (pp. 208-09). Her book proves that “with God all things are possible”. Her objective is not to give a historical account of Rwanda and/or of the genocide. She gives her own history. She attests that through God’s help forgiveness, even to those who killed her parents, is possible. Her book is meant to help people let go of the chains of hatred and anger so as to to be able to truly live in God who is love. Left to Tell is a breathtaking book that illustrates the fact that “the love of a single heart can make a world of difference” (p. 210). The book is divided into three parts, each of which has eight chapters. The author recounts how God saved her from the shadows of death and helped her discover who He really IS.